Problems Encountered in Femanine Primary School Headship in Marange in Mutare District. - Chityori, Annatoria Mukwekwe; V, Oyedele; Chikwature, Whatmore (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
The purpose of this study was to investigate and identify the problems faced by female head teachers in the management of primary schools in Marange area in Mutare district in Manicaland province. The mixed method research design was used which incorporate both qualitative and quantitative methods. The target population in this study were the female head teachers in Marange area in Mutare district, teachers and the Education Officer of Marange area in Mutare district. Marange area in Mutare district has 52 primary schools, of which seven (7) are headed by female head teachers. The researchers used questionnaires and interview guides for collection of data. The interview was targeted for female head teachers and Education Inspector of Marange area in Mutare district. The data that was obtained was both quantitative and qualitative. Majority of the teachers (75.0%) said that their perception towards their head teachers was good. Majority of the teachers (87.5%) noted that psychological traits do not bar the head teachers from performing school duties effectively. All of the teachers noted that the students accorded male and female teachers at the same level of respect. The following conclusions were drawn. Female head teachers are positively viewed by their teachers and students and are approachable since they encourage them to work to attain their goals in schools. Cultural and social barriers do interfere with the management of school affairs. Half (50%) of the head teachers said there was no role conflict between domestic and professional roles while 50% of head teachers felt that there was conflict. On the psychological factors influencing the head teachers’ performance, 87.5% of the teachers said that biological traits did not bar the head teachers from performing school duties. This was because they had a teaching experience, were assertive and aggressive. The study recommended that since female heads were positively viewed strongly by teachers, there is need for them to be given more posts of leadership in primary schools. Thus female head teachers are effective hence, they are able to achieve the goals of their respective institutions. Although cultural and social barriers may interfere with the management of school affairs, there is need for female heads to be encouraged to achieve leadership positions since they can manage the roles of leaders through mentorship.